Pengaruh Profitabilitas, Ukuran Perusahaan Dan Leverage Terhadap Nilai Perusahaan Pada Sub Sektor Tekstil Dan Garmen Yang Terdaftar Di Bei Tahun 2019-2023 - Duano, Putri Regina; Dama, Hais; Monoarfa, Mohamad Agus Salim (YUME : Journal of Management, 2024)
This study aims to find out how the influence of Profitability (ROA and ROE), Company Size (Total Assets), and Leverage (DAR and DER) on Company Value (Tobins'Q) on Textile and Garment Companies listed on the IDX in 2019-2023. The sampling technique taken was 18 Textile and Garment companies. The data collection technique in this study uses secondary data, namely financial report data that has been published by Textile and Garment companies on the Indonesia Stock Exchange (IDX). The analysis test used in this study is using Multiple Linear Regression Analysis and Descriptive Statistical Analysis using SPSS 26 application data analysis.Based on the research, the test results show that Profitability (ROA and ROE) has no effect on the company's value (Tobins'Q), the company's size (Total Assets) has a positive effect on the Company's Value (Tobins'Q), Leverage with the DAR gauge has a positive effect on the Company's Value (Tobins'Q) and Leverage with the DER gauge has no effect on the company's value (Tobins'Q). Keywords : Return On Aset, Return On Equity, Total Aset, Debt to Aset Rasio, Debt to Equity Rasio, dan Tobins’ Q